Novel Thienyl DPP derivatives Functionalized with Terminal Electron‐Acceptor Groups: Synthesis, Optical Properties and OFET Performance. Issue 25 (25th March 2022) - Fusco, Sandra; Barra, Mario; Gontrani, Lorenzo; Bonomo, Matteo; Chianese, Federico; Galliano, Simone; Centore, Roberto; Cassinese, Antonio; Carbone, Marilena; Carella, Antonio
Abstract: Three novel diketopyrrolopyrrole (DPP) based small molecules have been synthesized and characterized in terms of their chemical‐physical, electrochemical and electrical properties. All the molecules consist of a central DPP electron acceptor core symmetrically functionalized with donor bi‐thienyl moieties and flanked in the terminal positions by three different auxiliary electron‐acceptor groups. This kind of molecular structure, characterized by an alternation of electron acceptor and donor groups, was purposely designed to provide a significant absorption at the longer wavelengths of the visible spectrum: when analysed as thin films, in fact, the dyes absorb well over 800 nm and exhibit a narrow optical bandgap down to 1.28 eV. A detailed DFT analysis provides useful information on the electronic structure of the dyes and on the features of the main optical transitions. Organic field‐effect transistors (OFETs) have been fabricated by depositing the DPP dyes as active layers from solution: the different end‐functionalization of the dyes had an effect on the charge‐transport properties with two of the dyes acting as n‐type semiconductors (electron mobility up to 4.4 ⋅ 10 −2  cm 2 /V ⋅ s) and the third one as a p‐type semiconductor (hole mobility up to 2.3 ⋅ 10 −3  cm 2 /V ⋅ s). Interestingly, well‐balanced ambipolar transistors were achieved by blending the most performant n‐type and p‐type dyes with hole and electron mobility in the order of 10 −3  cm 2 /V ⋅ s Abstract : Three novel DPP derivatives characterized by terminal auxiliary acceptor groups have been reported. Because of their alternate donor‐acceptor molecular structure, the dyes are characterized by a low bandgap value up to 1.28 eV. The dyes, according to the different end functionalization, show a preferential unipolar charge transport behaviour with electron and hole mobility up, respectively, 4.4 ⋅ 10 −2 and 2.3 ⋅ 10 −3  cm 2 /V ⋅ s. Interestingly, in a blend configuration of the two best performant dyes, a well balanced ambipolar transport was observed.